2019
DOI: 10.26555/bahastra.v39i2.13573
|View full text |Cite
|
Sign up to set email alerts
|

Penggunaan metode demonstrasi Problem Based Learning (PBL) untuk meningkatkan keterampilan menulis teks prosedur

Abstract: Penelitian ini bertujuan mendeskripsikan peningkatkan penulisan teks prosedur pada siswa kelas XI MIPA 1 SMA Negeri 6 Yogyakarta dengan menggunakan metode demonstrasi Problem Based Learning (PBL). Metode penelitian ini merupakan penelitian tindakan kelas. Subjek penelitian adalah XI MIPA 1 SMA Negeri 6 Yogyakarta berjumlah 35 siswa. Penelitian ini terdiri dua siklus. Teknik pengumpulan data yang digunakan yaitu observasi, wawancara, tes menulis teks prosedur, dan dokumentasi. Analisis data menggunakan teknik a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Developing a procedural text is still considered difficult material to do. The factors that become the problems of students in producing procedural text include (1) students having difficulty in sorting the parts and steps of making a procedural text, (2) students still having difficulty in developing a procedural text by paying attention to linguistic aspects [7]. Also, learning to write is more emphasized on the results in the form of writing, not on the process when students write.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Developing a procedural text is still considered difficult material to do. The factors that become the problems of students in producing procedural text include (1) students having difficulty in sorting the parts and steps of making a procedural text, (2) students still having difficulty in developing a procedural text by paying attention to linguistic aspects [7]. Also, learning to write is more emphasized on the results in the form of writing, not on the process when students write.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the advantages of PBL, learning is more meaningful because students are faced with situations of applying concepts, integrating knowledge and skills of students, and can increase internal motivation to learn [9]. M. Hosnan suggests the stages of PBL namely student orientation to problems, organizing students to learn, guiding individual and group investigations, developing and presenting work, and analyzing and evaluating the problemsolving process [7]. Several studies have shown that learning with PBL very effective in improving student's writing skills in types of texts that require logical thinking, including procedural text [7], exposition text [11], explanatory text [12], observation report text [13], and description text [14].…”
Section: Introductionmentioning
confidence: 99%